1991
DOI: 10.1002/bit.260380912
|View full text |Cite
|
Sign up to set email alerts
|

Utility of culture redox potential for identifying metabolic state changes in Amino acid fermentation

Abstract: We investigated the relationship of dissolved oxygen and culture redox potential (CRP) on amino acid production. Corynebacterium glutamicum ATCC 14296 was used for all experiments. The fermentation can be divided into a growth phase and a production phase. Our results indicate that in order to get higher amino acid production, a lower oxygen supply during the exponential phase is favored. A higher oxygen supply rate appears to be necessary during the production phase. Culture redox potential (CRP) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Upon examining the off-line data, we observed that this discrepancy occurred when threonine was depleted (Figure IC). At this time, amino acid production commences, and in some cases (depending on oxygen availability), lactate formation reaches a maximum (Kwong and Rao, 1991 characteristics of CRP and do not contain information from a complete fermentation to check the profiles of CRP and DO. Contrary to Oktyabr'skii's reports, we did not observe any discrepancy between CRP and DO during glucose depletion in our fermentation system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon examining the off-line data, we observed that this discrepancy occurred when threonine was depleted (Figure IC). At this time, amino acid production commences, and in some cases (depending on oxygen availability), lactate formation reaches a maximum (Kwong and Rao, 1991 characteristics of CRP and do not contain information from a complete fermentation to check the profiles of CRP and DO. Contrary to Oktyabr'skii's reports, we did not observe any discrepancy between CRP and DO during glucose depletion in our fermentation system.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, all fermentations were carried out with Corynebacterium glutamicum ATCC 14296 at pH 7.2 and 30 "C in 5-L BioFlo I11 fermentors as previously described (Kwong and Rao, 1991). Data acquisition was on a Macintosh I1 computer.…”
Section: Methodsmentioning
confidence: 99%
“…Kwong and Rao have shown that reducing conditions can increase productions of homoserine and lysine by Clostridium glutamicum (13). In the same way, for Clostridium acetobutylicum, a decrease from Ϫ300 to Ϫ370 mV increases the production level of butanol and decreases those of butyrate and acetate (24).…”
mentioning
confidence: 95%
“…Certain enzyme activities are controlled by ORP, and modification of this parameter can alter metabolic balances during anaerobic growth in Escherichia coli [8]. This is also true for the synthesis of coproporphyrine by E. coli [9], and the proportion of amino acid synthesized by Clostridium glutamicum [10]. In addition to the regulation of some metabolic pathways, ORP can regulate the expression of genes as shown for the FNR system of E. coli [11].…”
mentioning
confidence: 99%